FUNGSI SURAT PERSETUJUAN PASIEN ATAS TERAPEUTIK MEDIK (PTM) DOKTER - Ari Purwadi; Harry Kurniawan Gondo (Perspektif, 2007)
Relation between doctor with patient have happened since ahead ( ancient Greek era), doctor as a giving medication to one who require it. This relation represent very personal based of trust of patient to doctor. Relation between doctor with this patient early from vertical relation pattern which starting from principle " best knows father" bearing relation having the character of is paternalistic.Ahead relation doctor position  with patient do not on an equal that is  higher position the doctor than patient because doctor assumed to know about everything related to disease and its healing. While patient do not know to the effect that that so that patient deliver its chance fully on-hand doctor. Contractual terms arise when patient contact doctor because he feel there is something that feeling of endangering its health.